Analisis Kebutuhan Angkutan Umum Rute Bekasi-Cikarang Jalur Pantura Terhadap Biaya Operasional Kendaraan (BOK): Analysis of Public Transport Needs On The Bekasi-Cikarang Pantura Route On Vehicle Operating Costs - Putra, Fahri Alif; Sri Nuryati; Yulius, Elma (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
The Pantura Highway which connects Bekasi City and Bekasi Regency is the main acces for community mobilization, so it is necessary to optimize services and public transport needs to fulfill the Bekasi- Cikarang route of ±15,1 km. Analysis of the optimal number of fleets is carried out using the Break Event Point (BEP) method by taking into account the value of load factor, BOK, daily income and number of existing fleets based on data from field interview surveys. The research results show that the number of public transportation operating in 80 units out of 112 units. Operation time 5 hours/day with operational cost of Rp. 447.700,91/day. The load factor value is 61,7% and the average speed is 16,6 km/hour. The Bok value  for the PCI method is Rp. 4.323.695,75 per 1000 km or Rp. 652.878,-/day. The BEP value for the optimal number of fleets with the existing in currently 62 unit and for the future in 2027 it is 60 units. The optimal fleet number using the PCI BOK method is currently 43 unit and 42 unit for 2027.